The photogrammetric survey for the knowledge of religious spaces. Geometrical and dimensional analysis of the cloister - G. Gioioso; L. Corniello (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
This research shows the photogrammetric survey and graphic documentation of the cloister of the Cathedral of the Assumption of the Virgin Mary and San Frutos in the city of Segovia, Spain. The building consists of a series of architectural elements dating back to the Renaissance period. Segovia Cathedral, dedicated to Our Lady of the Assumption and San Frutos, is a masterpiece of Gothic and Renaissance architecture. It represents an icon of the Christian faith and a cultural-historical point in Spanish history. The building was erected in the 16th century (1525–1577), when Renaissance architecture was flourishing in much of Europe. The research analyzes the context through the methodology of architectural drawing in order to propose knowledge and paths of fruition and enhancement. In the stages of the research, it was considered useful to divide the monumental building from the cloister in order to expand the possibilities of a more direct knowledge of the open layout towards the central courtyard. Particularly interesting is the system of vaults and buttresses that characterize the ceilings of the Cloister. The results achieved highlight an understanding of the vaulted system in relation to the planimetric space, completely divorced from the city and able to allow the passage of the religious in moments of solitude and prayer.